Control of a grid-assisted wind-powered hydrogen production system - Garcia Clua, Jose Gabriel (2010)
This paper deals with the control of a H2 production system supplied by wind power andassisted by the grid. The system architecture consists of a pitch-controlled wind turbinecoupled through a diode rectifier to an alkaline electrolyzer, which in turn is connected tothe electric grid through a fully-controlled bidirectional electronic converter. A controlstrategy for the electronic converter is proposed to regulate the electrolyzer current at itsrated value. Thus, H2 production efficiency is optimized despite wind power and temperaturevariability. Control design is based on sliding mode techniques, which are particularlyappropriate to control fast switching devices and exhibit strong robustness properties.Additionally, in high wind speeds, a pitch control loop is activated to limit the wind powercapture below admissible values.